2017
DOI: 10.1371/journal.ppat.1006762
|View full text |Cite
|
Sign up to set email alerts
|

What matters in chronic Burkholderia cenocepacia infection in cystic fibrosis: Insights from comparative genomics

Abstract: Burkholderia cenocepacia causes severe pulmonary infections in cystic fibrosis (CF) patients. Since the bacterium is virtually untreatable by antibiotics, chronic infections persist for years and might develop into fatal septic pneumonia (cepacia syndrome, CS). To devise new strategies to combat chronic B. cenocepacia infections, it is essential to obtain comprehensive knowledge about their pathogenesis. We conducted a comparative genomic analysis of 32 Czech isolates of epidemic clone B. cenocepacia ST32 isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 82 publications
3
49
1
Order By: Relevance
“…4D, Table S2). Notably, the magnitude of the latter effect is on par with observed differences between hypermutators, such as mutants deficient in the mismatch repair pathway, and their respective parent strains [45][46][47] .…”
Section: Impacts Of Pyocyanin On Antibiotic Tolerance and Resistance mentioning
confidence: 99%
“…4D, Table S2). Notably, the magnitude of the latter effect is on par with observed differences between hypermutators, such as mutants deficient in the mismatch repair pathway, and their respective parent strains [45][46][47] .…”
Section: Impacts Of Pyocyanin On Antibiotic Tolerance and Resistance mentioning
confidence: 99%
“…The adaptive mechanisms that allow these bacteria to colonize different host are still 442 uncertain, but Nunvar et al (2017) observed that the host immune system can modulate B. 443 cenocepacia evolution during chronic CF infection, since genes that encode proteins involved mutated in sputum isolates of CF-patients.…”
Section: Plant Beneficial Activities 389 390mentioning
confidence: 99%
“…could present the plasticity that allow them to occupy different niches. This 524 plasticity strategy can promote increasing fitness, and, once coupled with mutation and 525 selection, can result in a wide range of adaptation across contrasting environmental conditions 526 (Nunvar et al 2017). 527 528…”
Section: Plant Beneficial Activities 389 390mentioning
confidence: 99%
“…Preparation of sequencing libraries and whole-genome sequencing were performed as described in [3]. Sequencing reads were mapped to the complete reference genome of B. cenocepacia J2315 [28] using Geneious R9 platform [29].…”
Section: Whole-genome Sequencing and Data Analysismentioning
confidence: 99%
“…Patients with cystic fibrosis (CF) are among the ones at the greatest risk of contracting a Bcc infection. Bcc thriving in thick CF sputum are associated with chronic inflammation and significant decline in lung functions; infections with the most virulent Bcc lineages ultimately result in death due to a necrotizing septic pneumonia (cepacia syndrome) [2,3].…”
Section: Introductionmentioning
confidence: 99%